1970
DOI: 10.3126/nepjoph.v2i2.3714
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of refractive errors among the Nepalese population: a retrospective study

Abstract: Refractive errors progressively shift along myopia up to the third decade and change to hypermetropia till the seventh decade. Hyperopic shift in the refractive error in young adults should be well noted while planning any refractive surgery in younger patients with myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…17 Similar results showing myopia as the most common refractive error (68.2%) followed by hypermetropia (27.4%) was 6666seen in a study done in seen in a study done in Nepal medical college. 13 Similar preponderance of myopia over hypermetropia was seen in a study done on school children in Nepal.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…17 Similar results showing myopia as the most common refractive error (68.2%) followed by hypermetropia (27.4%) was 6666seen in a study done in seen in a study done in Nepal medical college. 13 Similar preponderance of myopia over hypermetropia was seen in a study done on school children in Nepal.…”
Section: Discussionsupporting
confidence: 65%
“…Similar findings showing most common ethnic groups as Brahmins, Gurungs, Newars were seen in a study in Pokhara. 17 Similar predominance of Brahmins and newars over other ethnic groups were seen in a study by KJD in Kathmandu. 21 Myopic astigmatism was more common than hypermetropic astigmatism.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, more myopia has also been reported among males (Shrestha et al. ), and some studies have observed no gender differences (Rezvan et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these school children, 450 were male and 397 were female. The screening is based on the Indiana school vision screening guideline [1][2][3] . Children unwilling to participate or absent during our visit were excluded from our study.…”
Section: Methodsmentioning
confidence: 99%